Non-linear Raman scattering intensities in graphene. Issue 9 (26th February 2020) - Giegold, Veit; Lange, Lucas; Ciesielski, Richard; Hartschuh, Achim
Abstract : The Raman G and 2D band intensities in graphene result from electronic-temperature dependent interference of quantum pathways. Abstract : We show that the Raman scattering signals of the two dominant Raman bands G and 2D of graphene sensitively depend on the laser intensity in opposite ways. High electronic temperatures reached for pulsed laser excitation lead to an asymmetric Fermi–Dirac distribution at the different optically resonant states contributing to Raman scattering. This results in a partial Pauli blocking of destructively interfering quantum pathways for G band scattering, which is observed as a super-linear increase of the G band intensity with laser power. The 2D band, on the other hand, exhibits sub-linear intensity scaling due to the blocking of constructively interfering contributions. The opposite intensity dependencies of the two bands are found to reduce the observed 2D/G ratio, a key quantity used for characterizing graphene samples, by more than factor two for electronic temperatures around 3000 K.